Kinetic Characteristics of Ignition Dispersed Condensed Substance Single Heated to a High Temperature of the Particles; European Physical Journal Web of Conferences (EPJ Web of Conferences); Vol. 110 : Thermophysical Basis of Energy Technologies - Glushkov D. O. Dmitry Olegovich (2016, 2016)
Title screen